HUBUNGAN MOTIVASI DAN SELF EFFICACY DENGAN HASIL BELAJAR MELALUI MODEL PEMBELAJARAN INKUIRI PADA POKOK BAHASAN KOLOID - Muhammad Ikhsan; Usman Usman; Iis Intan Widyowati; Indah Intan Permatasari N.S. (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2016)
Motivation and self efficacy closely related with wilness of student to study and having good result in studying. The study learning mode that could spur motivation & self efficacy is inquiry learning mode. This research is suppose to: (1) Determine relation between motivation and study result by using inquiry learning mode. (2) Determine relation between self efficacy and study result by using inquiry learning mode. (3) Determine relation between motivation and self efficacy with study result by using inquiry learning mode.This research was being held at SMA Negeri 5 Samarinda in 2014/2015 academic year by using associative quantitative method. This research sample determinated by purposive sampling technique. The amount of samples were 32 students of XI IPA 1 class as research samples. The Analysis result shows that the average percentation of motivation overall is 72,96%. The Analysis result shows that the average percentation of self efficacy overall is 77,27%. Motivation and study result  has middle degree correlation (0,495), self efficacy and study result has middle degree correlation (0,501), and also relation between motivation and self efficacy with study result has middle correlation degree (0,537). The significance statistic result of biserial correlation by using F test is 5,267. It means that Ftest= 5,267> Ftable=3,33.  This result means that motivation and self efficacy have positive relation, with the expected result these two factors could work together in studentselves to helping them to get the good result in study. Keywords:Motivation, Self Efficacy, Study Result, Inqiury